2016
DOI: 10.1177/0020872816663290
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life via social work: Influence of residential and community variables on life satisfaction

Abstract: The aim of this study is to assess the relationships between residential satisfaction (RS), sense of community (SOC), and citizen participation in a sample of 740 Spanish adults, and the impact these variables have on their life satisfaction (LS). The results show low levels of participation (social and community) and medium to high levels of LS, SOC, and RS. LS is positively affected by such situations as being in a relationship, being employed, and home ownership. It appears that positive socio-economic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This study also measured neighborhood satisfaction through these items. Finally, many studies have shown that demographic variables such as sex, age, monthly household income, and housing tenure affect QoL [4,6,19]. Therefore, this study also input these variables as control variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also measured neighborhood satisfaction through these items. Finally, many studies have shown that demographic variables such as sex, age, monthly household income, and housing tenure affect QoL [4,6,19]. Therefore, this study also input these variables as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been proven that homeowners have a higher QoL than renters do [17]. However, in addition to economic factors, the residential environments that residents encounter everyday have also been found to significantly affect QoL [18,19]. Specifically, most people primarily satisfy their needs and interests within their immediate residential areas [20][21][22]; thus, it could be surmised that residential environments also impact QoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction with life shares a common denominator with subjective well-being, psychological well-being and quality of life (Li et al , 2015; McAuley et al , 2000; Street et al , 2007; Trompetter et al , 2011). A higher level of satisfaction with life may trigger better health outcomes and quality of life (Moreno-Jiménez et al , 2017; Sirgy, 2012). A lower level of satisfaction with life may trigger depression and lower health outcomes (Lim et al , 2016; Lue et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%